Chronicle, Dissertations - Archives of Acoustics, Editorial Board (Archives of Acoustics, 1999)
1. Stanisław J. Pogorzelski, Ultrasound scattering for characterization of marine crude oil spills;2. Bogumił Bolesław Juliusz Linde, Acoustical spectroscopy of cyclic and heterocyclic compounds, ketones and polluted water surface;3. Anna Baranowska, Investigations of the finite amplitude wave propagation in water;4. Grzegorz Gondek, On the near field of ultrasonically diffracted light;5. Wiesław Jakubik, Surface acoustic wave propagation in selected phthalocyanine thin layers;